Nunn and Lumb's Applied Respiratory Physiology - Lumb, Andrew B; Thomas, Caroline; Slinger, Peter D (Elsevier, 2021)
The publication focuses on the physiology of the respiratory system and pulmonary diseases. Intended for professionals.
Keywords: Respiratory Physiological Phenomena; pneumologie a ftizeologie; fyziologie dýchací soustavy; plicní nemoci; fyziologie; Lung Diseases